PENGARUH STRATEGI BISNIS DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - Permana, Ridho; adhani, Ida; Susanti, Metta (Accounting Research and Business Journal, 2025)
This study aims to determine and analyze the influence of Business Strategy on Profit Management, the influence of Company Age on Profit Management, the influence of Profitability on Profit Management, the influence of Leverage on Profit Management, the influence of Business Strategy, Company Age, Profitability and Leverage on Profit Management. The data used in this study were obtained from the Financial Reports of Consumer Goods Industry Sector Companies Listed on the IDX for the 2020-2023 Period. The method used in this study is multiple linear regression involving the classical assumption test, followed by partial significance using the hypothesis test, namely the t-test, while to find out together the f-test is used at a significance level of 5%. The results of the study indicate that partially the variables Company Age have a significant effect on Earnings Management. While the variables Business Strategy, Profitability and Leverage do not have a significant effect on Earnings Management. Simultaneously the variables Business Strategy, Company Age, Profitability and Leverage have a significant effect on Earnings Management. The adjusted R squared value in this study is 0.508, which means that the ability of the independent variables to explain the variation of the dependent variable is 50.8% while the remaining 49.2% is explained by other independent variables outside the model.